Emotions associated with the first sexual relationship in gays and lesbians - Sánchez M., Ricardo (2020)
The objective of the present work was to evaluate in a sample of gays and lesbians, the emotions they experienced in their first sexual relationship, as well as the relationship with condom use, planning, consensus and age of sexual debut. 336 men and women participated, who responded online the Emotions, Stress and Coping questionnaire and some additional questions about their first sexual relationship. Significant differences were found in the emotions experienced by men and women, and among those who used a condom, they planned and agreed on their first sexual relationship. The results are discussed in terms of how emotions can affect the sex life of gays and lesbians.